HUBUNGAN TINGKAT NYERI DENGAN TINGKAT KECEMASAN PADA PASIEN POST OP SECTIO CAESAREA DI RUANG KEBIDANAN RUMAH SAKIT BHAYANGKARA PADANG TAHUN 2017 - NORA, RISTA (Menara Ilmu, 2018)
Post operation will cause pain and anxiety, so it is needed the act of caringindependent nurses to overcome these conditions. The purpose of this study was todetermine the Relationship of Pain With Anxiety Levels In Post Op Patients SectioCaesarea In Midwife Room Bhayangkara Hospital Padang Year 2017.This research is Analytical Descriptive with Cross Sectional Study approach. Thisresearch was conducted in Midwife Room of Bhayangkara Padang Hospital. The time ofthis study began in October 2016 until June 2017. The population of this study were allpost op cesarean caesarea patients are 78 people who are in the Midwife Room RSBhayangkara Padang. Sampling with Accidental Sampling.Results showed that as many as (41.0%) of respondents had a severe pain level andas many as (42.3%) of respondents had a severe anxiety level. Based on statistic test, pvalue <0,05 means that there is a significant relationship between pain level and anxietylevel (p = 0.02) in Midwife Room of Bhayangkara Padang Hospital 2017.Based on the results of this study it is also suggested to health workers to alwaysprovide support and motivation to every post op patient sectio caesarea that he canthrough the pain and anxiety that he felt after the operation was held.Reading list: 25 (1998-2014)Keywords: Pain Level, The Level Of Anxiety.